An Analysis of Politeness Strategies Used by Kit Connor in the Heart Stopper Series - Ferawaty Puspitorini; Haris Hamdani (Universitas PGRI Semarang, 2023)
In social situations, people must be able to recognize the faces of others to respond to emotions and maintain relationships. People are supposed to utilize politeness strategies to save their faces. The purpose of this research is to explain the different functions and kinds of politeness strategies utilized by Kit Connor in the television show The Heart Stopper. This study falls under discourse analysis and employs Brown and Levinson's theory of politeness strategies. In the form of utterances and words, this data is the script for the television series The Heart Stopper. According to our findings, Kit Connor's politeness strategy is used in 37 utterances. She used the baldness strategy 18.9% or 7 times of the time, positive politeness 54% or 20 times of the time, negative politeness 24.4% or 9 times of the time, and informally used 24.4% or 1 time of the time.2.7% used. Kit Connor's favourite politeness strategy is the